If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3 = 8 + -1x Reorder the terms: -3 + 8x = 8 + -1x Solving -3 + 8x = 8 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -3 + 8x + x = 8 + -1x + x Combine like terms: 8x + x = 9x -3 + 9x = 8 + -1x + x Combine like terms: -1x + x = 0 -3 + 9x = 8 + 0 -3 + 9x = 8 Add '3' to each side of the equation. -3 + 3 + 9x = 8 + 3 Combine like terms: -3 + 3 = 0 0 + 9x = 8 + 3 9x = 8 + 3 Combine like terms: 8 + 3 = 11 9x = 11 Divide each side by '9'. x = 1.222222222 Simplifying x = 1.222222222
| 69=2x+11+5x-5 | | 3x+6x=-12+1 | | X^3+4.5x^2+4.76x+0.78=0 | | 36x-9y=0 | | 9y-36x=0 | | 16=3w+1+w-1 | | 14x=-42 | | -x^2-8x+6=0 | | 5n-12=7n | | 1-m=23 | | 2x=4x-1 | | z=6+6I | | x^4+6.7x^3=0 | | 3*3X+(X-17)=64 | | 112=-7n | | 550x=8.25 | | 6f=2 | | 3d-5-2d=9 | | 2x-7=8x+12 | | 6x+14=50 | | 2X(5+1)=84 | | 5x+11=41 | | 0.50=b+0.39 | | r+12=3 | | 110=-10x | | Ln(6x+4)=2.7 | | 1+3x-(x-2)=3x+4 | | y=3.5+3x | | n+12=40 | | -9(3d-3)=+3 | | l-2=10 | | 2y=6x-7 |